High-resolution 3-D shape integration of dentition and face measured by new laser scanner - Sohmura, T.; Nagao, M.; Sakai, M.; Wakabayashi, K.; Kojima, T.; Kinuta, S.; Nakamura, T.; Takahashi, J. (IEEE Trans. Med. Imaging, 2004)
Face and dentition were measured using a high-resolution three-dimensional laser scanner to circumvent problems of radiation exposure and metal-streak artifacts associated with X-ray computed tomography. The resulting range data were integrated in order to visualize the dentition relative to the face. The acquisition interval for dentition by laser scanner was 0.18 mm, and complicated morphologies of the occlusal surface could be sufficiently reproduced. Reproduction of occlusal condition of upper and lower dentitions was conducted by matching the surface of the occlusal impression record with upper dentition data. To integrate dentition and face, a marker plate interface was devised and adopted on the lower dental cast or by the subject directly. Integration was performed by matching both sets of interface data. Reproduction of the occlusal condition and integration of the dentition and face were accomplished and visualized satisfactorily by computer graphics. The integration accuracy was examined by changing the attachment angle of the marker plate, and the marker plate attached at 45/spl deg/ showed the smallest error of 0.2 mm. The current noninvasive method is applicable to clinical examination, diagnosis and explanation to the patient when dealing with the physical relationship between face and dentition.